Efectos En La Presentación De Informes Financieros, Con La Aplicación Del “Catálogo De Clasificación Presupuestal Ccpet” En El Municipio De Cogua Del Departamento De Cundinamarca. - Guevara Osorio, Tatiana Katherine (Universidad Antonio Nariño, 2023)
Below is the degree work in which an analysis is made of the financial reports presented by the Municipality of Cogua (Cundinamarca) in the platform called CHIP of the General Accounting Office of the Nation, in the years 2020 and 2021, in order to to compare the management qualifications granted by the National Planning Department - DNP, in the Measurement of Municipal Performance before and after the implementation of the Budget Classification Catalog for Territorial Entities - CCPET.